The tommyknockers - Bieber, Jayne ([S.l.] : Konigsberg Sanitsky Production)
Summary: The small town of haven becomes a hot bed of inventions all run by a strange green power device. The whole town digging something up in the woods, and only an alcoholic poet can unphantom the secret of the tommyknockers.
Executive producer, Frank Konigsberg and Larry Sanitsky ; edited by Tod Feurman
Cast: Stephen King's, Jimmy Smits, Marg Hiegenberger, John Ashton
Keywords: Motion pictures; Suspense